PENGARUH STRATEGI PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA BIMBA SOLUSI KIDS UNIT CANDRABAGA BEKASI - Ratri Dwi Euisnawati; Nita Komala; Endah Prawesti Ningrum (Jurnal Ilmiah Akuntansi dan Manajemen, 2022)
This study aims to examine the effect of marketing strategy and service quality on customer satisfaction at Bimba Solutions Kids Unit Candrabaga Bekasi. The sampling used is as many as 130 consumers. The sampling technique is using the saturated sample technique and using the SPSS version 25 application. The results of this study indicate that the marketing strategy variable, namely 0.000 <0.05, has a positive and significant effect on consumer satisfaction. Service quality variable that is 0.000 <0.05 has a positive and significant effect on customer satisfaction at Bimba Solutions Kids Unit Candrabaga Bekasi. So it can be concluded that the marketing strategy and service quality have a simultaneous effect on customer satisfaction at Bimba Solutions Kids Unit Candrabaga Bekasi.